Implementation of Indonesian Defense Diplomacy in the South Pacific Region - Mahroza, Jonni; Widjayanto, Joni; Yulivan, Ivan; Prakoso, Lukman Yudo; Setiadi, Muhammad Ikmal (Journal of Legal and Cultural Analytics, 2023)
Domestically, Indonesia is also facing the dynamics of separatist movements and responding to cases of human rights violations in Papua, threats coming from support from Pacific countries for Papuan independence which then led Indonesia to create a "Look East Policy" as a form of its territorial defense efforts. This study utilized qualitative methods from scientific journals sourced from Google Scholar and official government websites which were then used as references in writing this article. Indonesia's defense efforts go through 2 aspects, namely external and internal. On the external side, the Indonesian government uses economic, cultural and defense diplomacy from the Indonesian Navy. To gather support from countries in the South Pacific and mitigate the risk of Papuan separatism becoming an international issue.